A Review on Autoimmune Diseases: Recent Advances and Future Perspectives - Balid Albarbar; Hanan Aga (AlQalam Journal of Medical and Applied Sciences, 2024)
Autoimmune diseases represent a diverse group of disorders characterized by immune-mediated attacks on the body’s own tissues and organs. This review provides a comprehensive overview of autoimmune diseases, covering their definition, classification, epidemiology, etiology, pathogenesis, clinical manifestations, current treatments, and future research directions. Autoimmune diseases can be categorized into organ-specific (e.g., type 1 diabetes, Hashimoto’s thyroiditis) and systemic (e.g., systemic lupus erythematosus, rheumatoid arthritis) conditions, each with distinct clinical presentations and underlying mechanisms. Genetic predisposition, environmental triggers, and immunological dysregulation play critical roles in disease development. Common symptoms include fatigue, joint pain, skin manifestations, and organ-specific dysfunction, contributing to significant morbidity and impaired quality of life. Current treatment strategies encompass immunosuppressive therapies, disease-modifying drugs, and emerging biologic agents targeting specific immune pathways. Advances in genomics, immunology, and precision medicine offer promising avenues for personalized diagnosis and treatment optimization. Future research directions include further elucidating disease heterogeneity, identifying novel biomarkers, and developing targeted immunotherapies to achieve long-term remission and improve patient outcomes. Understanding the complex interplay of genetic, environmental, and immunological factors is crucial for advancing therapeutic approaches and mitigating the global burden of autoimmune diseases. Enhanced collaboration across disciplines and continued investment in research are essential to translate these insights into clinical practice and benefit patients worldwide. الأمراض المناعة الذاتية هي مجموعة من الاضطرابات ناتجة عن هجمات مناعية على أنسجة الجسم وأعضائه. تقدم هذه الدراسة نظرة شاملة لأمراض المناعة الذاتية، تعريفها وتصنيفها وانتشارها ومسبباتها والعلامات السريرية والعلاجات واتجاهات البحث المستقبلي. يمكن تصنيف أمراض المناعة الذاتية الى أمراض خاصة بالأعضاء (مثل مرض السكري من النوع الأول والتهاب الغدة الدرقية هاشيموتو) وأمراض تصيب الأجهزة (مثل الذئبة الحمامية الجهازية والتهاب المفاصل الروماتويدي) ولكل من هذه الأمراض علامات سريرية متميزة وأليات مختلفة. يلعب العامل الوراثي والمحفزات البيئية وخلل التنظيم المناعي أدوارا حاسمة في تطور المرض. تشمل الأعراض الشائعة للمرض التعب، الام المفاصل، أعراض جلدية، والخلل الوظيفي في أعضاء محددة مما يساهم في حدوث المرض وخلل في الحياة. تشمل استراتيجيات العلاج المثبطات المناعية، والأدوية المعدلة للمرض، والعوامل البيولوجية الناشئة التي تستهدف مسارات مناعية محددة. يوفر التقدم في علم الجينات والمناعة والطب الدقيق طرقا واعدة للتشخيص الشخصي وتحسين العلاج. تشمل الاتجاهات البحثية المستقبلية مزيدا من توضيح عدم تجانس المرض، وتحديد المؤشرات الحيوية الجديدة، وتطوير علاجات مناعية مستهدفة لتحقيق وتطوير النتائج. فهم التفاعل المعقد بين العوامل الوراثية والبيئية والمناعية أمر بالغ الأهمية لتعزيز الأساليب العلاجية وتخفيف العبء العالمي لأمراض المناعة الذاتية. يعد التعاون المعزز عبر التخصصات والاستثمار المستمر في الأبحاث أمرا ضروريا لترجمة هذه الأفكار الى ممارسة سريرية ومساعدة المرضى في جميع أنحاء العالم